2017
DOI: 10.1111/pim.12453
|View full text |Cite
|
Sign up to set email alerts
|

Ascaris suum infection modulates inflammation: Implication of CD4+ CD25high Foxp3+ T cells and IL‐10

Abstract: Helminth infections have the ability to modulate host's immune response through mechanisms that allow the chronic persistence of the worms in the host. Here, we investigated the mechanisms involved on the suppressive effect of Ascaris suum infection using a murine experimental model of LPS-induced inflammation. We found that infection with A. suum markedly inhibited leucocyte influx induced by LPS into air pouches, suppressed secretion of pro-inflammatory cytokines (IL-1β, TNF-α and IL-6) and induced high leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…69,70 In both studies, mice were injected with 1 lg LPS with or without PCF supplementation into an air pouch and the researchers observed that helminth PCF prevented LPS-induced leukocyte influx and suppressed pro-inflammatory cytokine (IL-1b, TNF-a and IL-6) secretion. 69,70 In both studies, mice were injected with 1 lg LPS with or without PCF supplementation into an air pouch and the researchers observed that helminth PCF prevented LPS-induced leukocyte influx and suppressed pro-inflammatory cytokine (IL-1b, TNF-a and IL-6) secretion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…69,70 In both studies, mice were injected with 1 lg LPS with or without PCF supplementation into an air pouch and the researchers observed that helminth PCF prevented LPS-induced leukocyte influx and suppressed pro-inflammatory cytokine (IL-1b, TNF-a and IL-6) secretion. 69,70 In both studies, mice were injected with 1 lg LPS with or without PCF supplementation into an air pouch and the researchers observed that helminth PCF prevented LPS-induced leukocyte influx and suppressed pro-inflammatory cytokine (IL-1b, TNF-a and IL-6) secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Contrasting the probable induction of Th2 immune responses in humans, two mouse studies strongly support the potential of helminth PCF to induce robust Treg cell responses as well as increased IL-10 levels during LPS-induced inflammatory conditions. 69,70 In both studies, mice were injected with 1 lg LPS with or without PCF supplementation into an air pouch and the researchers observed that helminth PCF prevented LPS-induced leukocyte influx and suppressed pro-inflammatory cytokine (IL-1b, TNF-a and IL-6) secretion. Furthermore, helminth PCF supplementation has also been shown to induce Treg cells during non-LPS-induced inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms of the immune down‐regulatory effects of A. suum infection have been recently explored in a LPS‐induced inflammatory response in mice, finding that infection suppressed secretion of pro‐inflammatory cytokines (IL‐1β, TNF‐α and IL‐6) and induces high levels of IL‐10 and TGF‐β, as well as CD4 + CD25high, Foxp3 + T cells in the mesenteric lymph nodes. This has also investigated in pigs using transcriptomic analysis, showing that chronic A. suum infection induces suppression of inflammatory pathways in the intestinal mucosa, down‐regulating genes encoding cytokines, as well as antigen‐processing and co‐stimulatory molecules.…”
Section: Immunological and Clinical Influences Of Ascariasis On Asthmamentioning
confidence: 99%
“…The mechanisms of the immune downregulatory effects of A. suum infection have been recently explored in LPS (Lipopolysaccharide)-induced inflammatory responses in mice [25], finding that infection suppressed secretion of pro-inflammatory cytokines (IL-1β, TNF-α, and IL-6) and induced high levels of IL-10 and TGF-β as well as CD4+CD25highFoxp3+ T cells in the mesenteric lymph nodes. This has also been investigated in pigs using transcriptomic analysis, showing that chronic A. suum infection induces suppression of inflammatory pathways in the intestinal mucosa, downregulating genes encoding cytokines and antigen-processing and co-stimulatory molecules.…”
Section: Helminth-driven Immunomodulationmentioning
confidence: 99%